Proceso de envagelización para los jóvenes de octavo de básica. Estudio de caso en la unidad educativa a distancia Mario Rizzini - Pinos Verdugo, Santiago (2013)
This study is a response to the pressing need to show the figure of Jesus to young people, and in this particular case to the students of Unidad Educativa a Distancia Mario Rizzini. The evangelist intentions have been put aside by many factors such as: an irregular process of ongoing training by tutors, lack of missionary identity, lack of awareness of the process of distance education and evangelization, the intention to apply a regular educational model to distance education, etc. In these contexts, I can affirm with full insight, that as Salesians, we have had very low percentages in these aspects. A suggestion to achieve the desired evangelization is to use a different knowledge process applied to students. This process is deeply thoughtful and based on the Gospel message and church invitations to release Jesus as a model and leading figure in his encounter with the world of youth. How to do this? To answer this question, we advocate a modular approach that enables students to be interested in discovering the path that leads us to live in Christ through real situations and examples of clear, reasoned discussion,